The special role of education in the development of intercultural competences - comparative analysis of the results of interviews with students from different European countries - Agnieszka Knap-Stefaniuk; Ewa Agata Sowa-Behtane; Joan Sorribes; Josep Boyra; Caterina De Lucia; Pasquale Pazienza (Multidisciplinary Journal of School Education)
Research objectives and problem(s): This article aims to describe the role of education in developing students’ intercultural competences. The research problem addresses the question: How do students perceive the importance of education (university studies) in shaping intercultural competences necessary for their future careers?